Prevalence of Chronic kidney disease in patients with chronic obstructive pulmonary disease in Tishreen University Hospital (Latakia University Journal -Medical Sciences Series, 2022)
Background: Cardiovascular diseases, osteoporosis, and depression are identified comorbidities of chronic obstructive pulmonary disease (COPD), but there have been few reports of chronic kidney disease (CKD) as a comorbidity of COPD. Aim: The objective of this study was to investigate the prevalence of CKD in COPD patients using estimated glomerular filtration rate (eGFR) based on creatinine. Materials and Methods: The current study included 150 stable COPD patients. They were enrolled in the study during their follow up visits to the outpatient clinic of the Chest Department, Tishreen University Hospital from April 2020 to April 2021. The eGFR was estimated and patients were categorized according to their renal function as having normal renal function (eGFR ≥ 60 mL/min/1.73 m2), or chronic kidney disease (eGFR < 60 mL/min/1.73 m2). Patients with diabetes mellitus and hypertension were excluded. Results: The mean age of patients was 64.7 ±6.8 years, 37.3% of them were females. The overall prevalence of CKD (eGFR